2003
DOI: 10.1111/j.1572-0241.2003.08700.x
|View full text |Cite
|
Sign up to set email alerts
|

Once-weekly epoetin alfa improves anemia and facilitates maintenance of ribavirin dosing in hepatitis C virus-infected patients receiving ribavirin plus interferon alfa

Abstract: In anemic HCV-infected patients treated with RBV/IFN, epoetin alfa increases Hb levels and maintains RBV dosing. Based on these results, epoetin alfa seems to be promising in the treatment of HCV treatment-related anemia. Further research is warranted to determine the potential impact on outcomes, including quality of life and sustained viral response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 24 publications
6
112
0
Order By: Relevance
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Discussionsupporting
confidence: 58%
“…However, some studies have used decision analysis to estimate the cost-effectiveness of adjunctive therapy with erythropoietic growth factor (EGF) compared with that of standard care in the treatment of hepatitis C. The use of EGFs appears to be costeffective in patients with anaemia who are receiving combination therapy for HCV genotype 1, 2 or 3. Compared with The results of previous studies [27,28,30,37,49,50,52,[56][57][58] and the present study have shown that the introduction of Epoetin Alpha therapy in patients treated with PEG-interferon alpha-2A and RBV for CH related to genotype 1b HCV infection leads to an improved adherence to treatment, and, consequently, to a significant improvement of SVR.…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…Several studies demonstrated the efficacy of rHuEPO in decreasing anemia in RBV-treated patients. 84,85 Another study confirmed similar efficacy for darbepoetin alpha, which was used for treatment of RBV-induced anemia. 86 Pockros et al 87 demonstrated that patients receiving rHuEPO who had the largest increases in hemoglobin concentrations during the course of the study also had the greatest improvements in HRQL.…”
Section: Side Effects Of Chc Treatment and Their Managementmentioning
confidence: 63%
“…Studies indicate that therapy with erythropoietin at the dosage of 40,000 IU once a week elevates the level of Hb after one week of use and thus permits the maintenance of RBV dosage in patients that become anemic during combined therapy for hepatitis C [12,13]. In the study conducted by Afdhal et al, the initial dose of RBV was maintained in 88% of the patients who received erythropoietin during treatment for hepatitis C, and Hb levels increased (from 10.6 ± 0.9 to 13.2 ± 1.2 g/dL) in those same patients [13].…”
Section: Adverse Event Approximate Incidence (%)mentioning
confidence: 99%